ANALYSIS OF THE USE OF ONLINE LEARNING MEDIA ON LEARNING SATISFACTION FOR TEACHERS AND STUDENTS AT ISLAMIC ELEMENTARY SCHOOL - Nisak, Nur Maslikhatun; Supriyanto, Eko Budi; Astuti, Ruli; Nafi', Dhikrillahi Ilmun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to investigate the impact of online media usage on teacher satisfaction in the context of education influenced by the COVID-19 pandemic. The pandemic has forced the education sector to transition from face-to-face interactions to the predominant use of online systems in the teaching and learning process at all levels of education. Google Classroom emerged as the primary choice for online learning media among respondents during the pandemic. The research employed a descriptive quantitative method using Partial Least Squares (PLS) for data analysis, including validity tests, reliability tests, multiple linear regression analysis, and t-tests. The research results indicate a positive correlation between the use of online media and learning motivation with teacher satisfaction. As the quality of online media usage by teachers increases, so does their satisfaction. The conclusion of this study supports the hypothesis that the adoption of online media in the learning process significantly contributes to teacher satisfaction. This research provides valuable insights in the context of education influenced by the pandemic, highlighting the importance of effective choices in online learning media and understanding their impact on teacher satisfaction. Keywords associated with this research include pandemic impact, online education, teacher satisfaction, students, and learning motivation.